ENGARUH MODEL PEMBELAJARAN AKTIF COURSE REVIEW HORAY TERHADAP HASIL BELAJAR BIOLOGI SISWA KELAS VIII SMP NEGERI 10 BATAM - Ramses Ramses; Nurhaty Purnama Sari; Harni Lainy Br.Bakkara (SIMBIOSA, 2014)
This study aims to know the influence of active learning model Course Review Horay to biology learning outcomes at eighth grade students of SMP Negeri 10 Batam academic year 2013/2014. This research design is  randomized experiment using posttest only control-group design. The study population is all the eighth grade students of  SMP Negeri 10 Batam with reached population consist of 7 classes. The sampling technique using a simple random sampling. Samples were selected class VIII5 as control class and VIII8 as experiment class. The instrument  that use in this research is the form of the test. Requirement have been in the form of normality and homogeneity test, which showed that normal and homogeneous data. Technique of data analysis conducted by the t test. The result analysis of data using the t test showed the tvalue 3.01 and ttable is 2.00 (tvalue ttable). The results showed that the active learning result model Course Review Horay give effect to increase student learning outcomes from the average of the experimental class 82,57 and control class 76,04. Thus, the hypothesis put forward acceptable significance level (α = 0.05). Thus, it can be concluded that the using of active learning model Course Review Horay influential on learning outcomes of biology at eighth grade students of SMP Negeri 10 Batam. Keywords: Course Review Horay, Biology Learning Outcomes.